Discourse Style of Nigerian Coup Plotters - Anyachonkeya, Ngozi; Nwosu-Okoli, Ifeoma (European Scientific Journal, ESJ, 2023)
This essay examines the discourse style of Nigerian coup plotters. For more than two decades the military junta dominated the political landscape of Nigeria, during which they informed Nigerians of their sustained takeover of government from the discredited civilian or military predecessors. As they ruled through the barrel of the guns, they outsmarted the civilian politicians in corruption, executive lawlessness, culture of impunity and reckless irresponsibility. They shed the blood of their military comrades in sheer lust for power and constituted themselves into tin gods. This paper investigates selected speeches of Nigerian coup plotters with a view towards ascertaining their discourse styles. The paper speculates that the broadcast idiolect revolves around propaganda, polemic and discursive styles as well as a style which this paper calls fox, Tartuffe or tortoise through which they intimidate their opponents and the civilian populace into submission. This paper, by its nature, involves both qualitative and quantitative kind of research as it relies heavily on observation nd library research. The military class succeeded in intervention mission but failed abysmally in the thrust of salvation. Their selfish quest made them neocolonialists in military garb. This paper, therefore, argues that their dismal failure in political governance of their father land ends up leaving the masses much poorer and more disillusioned than they had been under the corrupt civilian government. The unmitigated disaster the military precipitated in political governance constrained Nigerian literary patriots to publish social satires – in all genres - amidst propaganda; they reprehensively indict the military villains and keep calling for a revolution from the disconsolate Nigerians.